PENGARUH MODEL OPEN ENDED DAN MEDIA KONKRET TERHADAP MINAT BELAJAR SISWA PADA PEMBELAJARAN MATEMATIKA DI SEKOLAH DASAR - Riska Nanda Putri Kastiar; Firman; Desyandri (STKIP Subang, 2024)
The objectives of the study: (1) describe the interest in learning mathematics with the open ended and media concrete models, (2) compare the influence of the open ended and media concrete models on interest, (3) compare the influence of learning styles on interests, (4) determine the influence of interactions between teaching methods and learning styles on interests. The study used a pseudo-experimental research design with two experimental groups, namely open ended and media concrete. Research instruments in the form of questionnaires, while the data analysis technique uses multivariate analysis, two-way factorial design with unequal cells, and further tests with Bonferroni procedures. The results of this study are as follows: (1) the open ended and media concrete models are good for increasing students' interest in learning mathematics, (2) media concrete is better than the open Ended learning method in terms of student learning interest, (3) there is an influence of learning styles on student learning interests, with visual learning styles having better learning interests than auditorial learning styles, (4) there is no influence of interaction between learning methods and students' mathematics learning styles on students' interest in learning mathematics.